Transforming Ethnographic Knowledge - Clarke, Kamari Maxine, 1966-; Hardin, Rebecca (Book collections on Project MUSE., 2012)
The ethnographic methods that anthropologists first developed to study other cultures-fieldwork, participant observation, dialogue-are now being adapted for a broad array of applications, such as business, conflict resolution and demobilization, wildlife conservation, education, and biomedicine. In Transforming Ethnographic Knowledge, anthropologists trace the changes they have seen in ethnography as a method and as an intellectual approach, and they offer examples of ethnography's role in social change and its capacity to transform its practitioners. Senior scholars Mary Catherine Bateson.